Prehod od ekspresionizma k novi stvarnosti, kot ga vidi France Vodnik - Mikeln, Zala (Slavistična revija, 2004)
The paper deals with the comprehension of Expressionism and New Reality as presented in France Vodnik's publicistic works in literary criticism and literary history. It also discusses his evaluation of individual literary works and his view of art in general, in which it detects considerable influence of the crusader mentality.
Keywords: ekspresionizem; Expressionism; history of literature; literarna kritika; literarna zgodovina; literary criticism; nova stvarnost; Slovene literature; slovenska književnost; Vodnik, France, 1903-1986